Laryngeal Relativism predicts Italian - Berces, Katalin Balogne; Huszthy, Balint (Yearbook of the Poznan Linguistic Meeting, 2018)
However, in the “classical” version of [sg] languages (e.g., English), no laryngeal activity in the form of any kind of spreading is attested, which suggests the absence of any source element and, instead, a dominant role of obstruency (|h|). We, therefore, arrive at a three-way typology: h-systems, H-systems and L-systems. At the same time, arbitrary phonetic interpretation in LR predicts the existence of, e.g., h-systems with virtually no aspiration in the fortis series. We claim that this is indeed the characterisation of Italian. Using data from potential feature spreading situations, elicited in loanword and foreign accent settings, we show that Italian is an h-system, exhibiting no true laryngeal activity.